A Study on Fuzzy Relational Mapping (FRM) - Abinaya, m; Ramadass, v (International Journal of Computer Sciences and Engineering, 2025)
The fuzzy model is a limited arrangement of fuzzy relations that frame a calculation for deciding the yields of a procedure from some limited number of past data sources and yields. Fuzzy model can be utilized as a part of connected mathematics, to contemplate social and mental issue and furthermore utilized by specialists, design, researchers, industrialists and analysts. There are different sorts of fuzzy models. In this paper we utilize two fuzzy models and give their application to a genuine issue. In this paper two methodologies of fuzzy capacity have been researched: the first distinguishes a fuzzy capacity with a special fuzzy relation (we call it an (E − F)- fuzzy capacity), and the second one characterizes a fuzzy capacity as a conventional mapping between fuzzy spaces. In our exchange the components of the area space are taken from the genuine vector space of measurement n and that of the range space are genuine vectors from the vector space of measurement (m when all is said in done need not be equivalent to n). We mean by R the arrangement of hubs R1, … , Rm of the range space, where Ri = (x1, x2, … , xm)/xj = 0 or 1 for i = 1, … ,m. In the event that xi = 1 it implies that the hub Ri is in the ON state and if xi = 0 it implies that the hub Ri is in the OFF state.